Peran Kemenko Perekonomian dalam Memberdayakan Pesantren : Analisis Hukum Ekonomi Pancasila - Anissa Nur Fadhilah; Nabila Khusnul Hidayah; Fatimatusholikhah Fatimatusholikhah; Hanifah Rahmawati (Majelis: Jurnal Hukum Indonesia, 2025)
Islamic boarding schools (pesantren) are religious institutions focused on education, the dissemination of Islamic knowledge, and the propagation of Islamic propagation, as well as serving as centers for the development of religious thinkers. Furthermore, pesantren also serve as platforms for human resource development and empowerment for alumni, families, and the wider community. This research aims to collect data to uncover fundamental issues arising from phenomena, realities, and experiences, thereby providing a diverse range of knowledge regarding the life and practice of pesantren-based economic empowerment. Economic empowerment is understood as both a process and a goal. As a process, economic empowerment encompasses a series of efforts to improve the economic capabilities and strengths of vulnerable communities to improve their quality of life. As a goal, economic empowerment represents the desired condition or outcome and serves as a measure of the success of the process. To realize an empowered people's economy, three main elements are required: production potential, distribution potential, and consumption potential. These three elements constitute concrete and applicable steps for effectively implementing community economic empowerment. By considering these three potentials, empowerment can be implemented in a focused and sustainable manner. Pesantren, in their historical and cultural dynamics, play a vital role in the life of the nation. Therefore, Islamic boarding schools have the capacity, both in quality and quantity, to contribute and play a significant role in efforts to empower the community's economy.